2013
DOI: 10.1111/bjh.12260
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term treatment with romiplostim in patients with chronic immune thrombocytopenia: safety and efficacy

Abstract: SummaryRomiplostim was effective, safe, and well-tolerated over 6-12 months of continuous treatment in Phase 3 trials in patients with immune thrombocytopenia (ITP). This report describes up to 5 years of weekly treatment with romiplostim in 292 adult ITP patients in a long-term, single-arm, open-label study. Outcome measures included adverse events (including bleeding, thrombosis, malignancy, and reticulin/fibrosis), platelet response (platelet count >50 9 10 9 per litre), and the proportion of patients requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
243
2
24

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 243 publications
(293 citation statements)
references
References 31 publications
24
243
2
24
Order By: Relevance
“…From the whole population of patients exposed to romiplostim in all 13 company-sponsored trials, a subanalysis was carried out by Kuter et al on 291 patients who entered a long-term study after the completion of a previous ITP study with romiplostim [34]. Patients were followed for up to 5 years (mean exposure time 2.11 years) to assess safety and efficacy.…”
Section: Thrombotic Risk and Tpomentioning
confidence: 99%
“…From the whole population of patients exposed to romiplostim in all 13 company-sponsored trials, a subanalysis was carried out by Kuter et al on 291 patients who entered a long-term study after the completion of a previous ITP study with romiplostim [34]. Patients were followed for up to 5 years (mean exposure time 2.11 years) to assess safety and efficacy.…”
Section: Thrombotic Risk and Tpomentioning
confidence: 99%
“…Into each arm of the IgG heavy chain are inserted two identical 14-amino acid peptides with the sequence IEGPTLRQWLAARA [66]. Glycine linker regions are also shown [66] romiplostim in most studies was 4-5 lg/kg [45,[71][72][73], this author recommends starting at 3 lg/kg in most settings and increasing by 2 lg/kg weekly until the desired platelet count is attained. In more urgent settings even higher starting doses, including the maximal dose of 10 lg/kg, may be used to determine rapidly if this agent will be effective in the patient.…”
Section: Romiplostimmentioning
confidence: 99%
“…This is based upon a large number of clinical trials that have shown that the administration of either TPO receptor agonist increases the platelet count (Fig. 6), decreases the need for rescue medications, decreases the need for other ITP therapies such as corticosteroids, may avoid the need for splenectomy, improves the quality of life, and markedly decreases the rate of bleeding [45,71,[87][88][89].…”
Section: Clinical Development Of Tpo Receptor Agonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ancak TPO reseptor agonistleri ile ilgili son yapilan çalişmalarda; İTP hastalarinda TPO reseptor agonistleri kullanimi sonucu venöz tromboemboli gelişimi açisindan plasebo grubuna göre anlamli fark saptanmamiştir [19,21,22,23].…”
Section: Olguunclassified